A Study on Smart Wheelchair Systems - Alsibai, Mohammad Hayyan; Abdul Manap, Sulastri (Penerbit Universiti Malaysia Pahang, 2015)
Many people are suffering of temporary or permanent disabilities due to illnesses or accidents. For cases of difficult or impossible walking, the use of a wheelchair is becoming essential. Manual or electrical wheelchairs are satisfying for most of the low and medium level disability case where patients can use the wheelchair independently. However, in severe cases, it is difficult or impossible to use wheel chairs independently. In such cases wheelchair users often lack independent mobility and rely on somebody else handle the wheelchair. Researchers involved in wheelchair are aiming at designing smart wheelchairs to solve such problems. This paper is to review the recent studies on smart wheelchair systems. It aims to evaluate the current available technologies and to discuss new future directions for our ongoing research project.